Mortality in Plantations of Dalbergia sissoo Raised from Seedlings and Clonal Material - Shukla, A. N. (Indian Forester, 2003)
The pathological symptoms developing in the trees of Dalbergia sissoo (Shisham) in plantations raised from the seedlings and clonal material in a high mortality area were compared. The seedling plantation raised on an ideal site along river Gaula at Haldwani showed stem cankers , bands and oozing of dark pitch. But there was no yellowing of leaves , wilting and dying of trees. On the other hand , plantation raised from the clonal material showed yellowing of leaves and outright killing of trees up to 32%. But no stem infection of any kind was observed. The area was leased for agroforestry. This practice damaged the stem and roots causing infection and subsequent mortality.